2021
DOI: 10.1186/s12935-021-02144-y
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs involved in the STAT3 pathway in glioma

Abstract: Glioma is the most common malignant primary brain tumour in adults. Despite improvements in neurosurgery and radiotherapy, the prognosis of glioma patients remains poor. One of the main limitations is that there are no proper clinical therapeutic targets for glioma. Therefore, it is crucial to find one or more effective targets. Signal transducer and activator of transcription 3 (STAT3) is a member of the STAT family of genes. Abnormal expression of STAT3 is involved in the process of cell proliferation, migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 105 publications
0
17
0
Order By: Relevance
“…STAT3 activation has been observed in many human cancers, including breast, melanoma, and thyroid cancer 50 , 51 . Evidence points to STAT3 playing a critical role in GBM development and progression 52 , and its transcriptional activation is regulated by IL-6-mediated JAK2 27 . STAT3 is an oncogenic transcription factor whose structural and persistent activation of its proteins is highly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 activation has been observed in many human cancers, including breast, melanoma, and thyroid cancer 50 , 51 . Evidence points to STAT3 playing a critical role in GBM development and progression 52 , and its transcriptional activation is regulated by IL-6-mediated JAK2 27 . STAT3 is an oncogenic transcription factor whose structural and persistent activation of its proteins is highly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that Stat3 and miR-21 closely interact, 40 and the complex interplay between non-coding RNAs (including miR-21) and Stat3 related to its function in glioma has recently been thoroughly reviewed. 41 Moreover, miR-21 downregulates human telomerase reverse transcriptase expression through its action on Stat3, inhibiting glioma cell growth. 42 Therefore, glioma cells lacking miR-21 might upregulate the Stat3 pathways involved in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The ncRNAs can be classified into small ncRNAs (sncRNAs, 18-200 nt), lncRNAs (>200 nt), and circRANs with a unique loop structure, based on the 200 nt cut-offs of their mature transcript length ( Bian et al, 2021 ). The small ncRNAs can be divided into small nuclear RNAs (snRNAs), small nucleolar RNAs (snoRNAs), miRNAs, and piRNAs ( Pinho et al, 2022 ).…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 99%